Probing the Influence of Novel Organometallic Copper(II) Complexes on Spinach PSII Photochemistry Using OJIP Fluorescence Transient Measurements - Sergei K. Zharmukhamedov; Mehriban S. Shabanova; Irada M. Huseynova; Mehmet Sayım Karacan; Nurcan Karacan; Hande Akar; Vladimir D. Kreslavski; Hesham F. Alharby; Barry D. Bruce; Suleyman I. Allakhverdiev (Biomolecules, 2023)
Modern agricultural cultivation relies heavily on genetically modified plants that survive after exposure to herbicides that kill weeds. Despite this biotechnology, there is a growing need for new sustainable, environmentally friendly, and biodegradable herbicides. We developed a novel [CuL2]Br2 complex (L = bis{4H-1,3,5-triazino[2,1-b]benzothiazole-2-amine,4-(2-imidazole) that is active on PSII by inhibiting photosynthetic oxygen evolution on the micromolar level. [CuL2]Br2 reduces the FV of PSII fluorescence. Artificial electron donors do not rescind the effect of [CuL2]Br2. The inhibitory mechanism of [CuL2]Br2 remains unclear. To explore this mechanism, we investigated the effect of [CuL2]Br2 in the presence/absence of the well-studied inhibitor DCMU on PSII-containing membranes by OJIP Chl fluorescence transient measurements. [CuL2]Br2 has two effects on Chl fluorescence transients: (1) a substantial decrease of the Chl fluorescence intensity throughout the entire kinetics, and (2) an auxiliary “diuron-like” effect. The initial decrease dominates and is observed both with and without DCMU. In contrast, the “diuron-like” effect is small and is observed only without DCMU. We propose that [CuL2]Br2 has two binding sites for PSII with different affinities. At the high-affinity site, [CuL2]Br2 produces effects similar to PSII reaction center inhibition, while at the low-affinity site, [CuL2]Br2 produces effects identical to those of DCMU. These results are compared with other PSII-specific classes of herbicides.